Online Seminar on Dental Health Management in Early Childhood Education Students (2–6 Years Old) - Sinaredi, Betadion Rizki; Hasnarani, Syafira; Septianingtyas, Virna; Priananda, Gearel (Indonesian Journal of Dental Medicine, 2020)
Background: Dental injuries can affect children's development both physically, psychologically and in social interactions, so it requires proper treatment. However, the lack of knowledge of parents and teachers about handling dental injuries in children is considered to worsen the condition of teeth and mouth after injury. Purpose: This activity aims to increase the knowledge of teachers in providing emergency dental management for children aged 2-6 years. Methods: This activity is in the form of online health education that involves early childhood, education teachers. Health education is carried out using the lecture method and discussion on emergency management and dental health in children. Increasing knowledge of activity participants was assessed using the google form provided before and after the activity was carried out. Results: This community empowerment activity shows an increase in the knowledge of teachers about health and dental emergencies in children after being given dental health education interventions (66.7%). This activity also found a decrease in the number of teachers with low levels of knowledge (33.3%). Conclusion: The increase in teachers' knowledge in providing dental emergency management in children can be caused by the use of accessible media and easy-to-understand module forms.